Multilateral trade liberalisation, foreign direct investment and the volume of world trade - David R. Collie (Cardiff University, Cardiff Business School, 2010)
A paradox in international trade is that multilateral trade liberalisation has resulted in increases in both the volume of world trade and the amount of foreign direct investment (FDI). This note presents a Cournot duopoly model with two regions, each consisting of two countries, and with an inter-regional transport cost. It is shown that multilateral trade liberalisation may lead firms to switch from exporting to undertaking export-platform FDI when the interregional transport cost is high. Also, when the inter-regional transport cost is high, the switch to FDI leads to an increase in the volume of world trade in this industry.
Keywords: F12; F13; F23; 330; Trade Liberalisation; Foreign Direct Investment; Cournot Oligopoly; Internationale Handelspolitik; Außenhandelsliberalisierung; Direktinvestition; Duopol; Theorie